THE EFFECTIVENESS OF PPP (PRESENTATION, PRACTICE, PRODUCTION) METHOD IN TEACHING ENGLISH VOCABULARY - Moh. Hilman Fikri; Ali Shohibul Umar; Mohammad Ilham Yasin; Wahyu Sudrajad (EDUCATUM: Scientific Journal of Education, 2023)
The scattered of English throughout the world signaled the language significance. Thus, the current study aims to improve junior high school vocabulary mastery in TEFL. A random sampling technique under pre-experimental design was employed to select one class out of the eight classes. The study then recruited 21 students. Vocabulary test in the form of multiple choices was implemented as the instrument of the study, consisted of 50 items. The test was administrated twice. The first test was pre-test and the second test was post-test to see the method significance difference. Moreover, the results of the pre-test and post-test were analyzed by using t-test. Based on the study, the data analysis on the students’ score in pre-test unpacked that the mean score of the pre-test was 45.61, the mean score of post-tests was 67.52, the t-value was 79.56, and the t-value in the table was 17.25. Therefore, the finding of the research showed that the use of PPP method may increase EFL vocabulary mastery, indicating accepted hypothesis.